Relationally embedded anxiety in emerging adulthood: a multilevel developmental systems model - Angela CALANCEA; Robert CALANCEA (Acta et Commentationes, Sciences of Education, 2026)
Emerging adults (18–30 years) experience a developmental stage characterized by identity consolidation, relational fluidity, prolonged neurobiological maturation, and intensified sociocultural exposure [5]. During this period, anxiety prevalence reaches elevated levels and frequently co-occurs with relational instability and attachment insecurity. Existing explanatory models remain fragmented across cognitive-behavioral, attachment-based, neurobiological, and sociocultural perspectives. This integrative review proposes a multilevel developmental systems framework conceptualizing anxiety as a relationally embedded and dynamically co-regulated phenomenon [7]. Neuroregulatory asymmetry, attachment activation, relational turnover, and digital ambiguity amplify bidirectional feedback loops between anxiety and maladaptive relational behaviors, while protective factors support developmentally anchored personalized interventions.